Digital Transformation and Innovation in Teaching and Learning in Entrepreneurship Education in Higher Education Institutions - Sziegat, Hongmei (Finland, 2025)
This study provides state-of-the-art and future perspectives on digital transformation and inno-vation in teaching and learning in entrepreneurship education in higher education institutions. It conceptualizes a hybrid teaching framework for digital transformation and innovation in en-trepreneurship education including integrating AI solutions, MOOCs, online learning plat-forms, serious games, virtual simulation games, and social media into teaching and learning in entrepreneurship education besides integrating digital technology and pedagogy into teaching and learning to innovate teaching and learning in entrepreneurship education in higher educa-tion institutions. Digital transformation and innovation aim to enhance the effectiveness and quality of inclusive and equitable entrepreneurship education for continuous quality improve-ment and sustainable development.
Conference Proceedings : 22nd Nordic Conference on Small Business Research